2018
DOI: 10.1007/jhep08(2018)150
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the parameters in MSSM

Abstract: In the present work we search for renormalization group invariant relations among the various massless and massive parameters of the Minimal Supersymmetric Standard Model. We find that indeed several of the previously free parameters of the model can be reduced in favor of few, the unique gauge coupling and the gaugino mass at the unification scale among them. Taking into account the various experimental constraints, including the B-physics ones, we predict the Higgs and the supersymmetric spectrum. We find th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 145 publications
0
16
0
1
Order By: Relevance
“…However, the decoupling in the Higgs sector could mean that evidence of a non-minimal sector is out of reach. In a recent paper analysing MSSM parameters, Heinemeyer et al (2018) came to the following conclusion about the prospects of ruling out heavy Higgses:…”
Section: A Comparison With Minimal Supersymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the decoupling in the Higgs sector could mean that evidence of a non-minimal sector is out of reach. In a recent paper analysing MSSM parameters, Heinemeyer et al (2018) came to the following conclusion about the prospects of ruling out heavy Higgses:…”
Section: A Comparison With Minimal Supersymmetrymentioning
confidence: 99%
“…The SUSY and heavy Higgs particles will likely escape the detection at the LHC, as well as at ILC and CLIC. (Heinemeyer et al, 2018) Data indicates that if there is an extended Higgs sector, then the heavy Higgses will be too heavy to detect and while physicists are precisely probing the SM for deviations, it may be that conclusive support for a minimal Higgs will not be forthcoming, even at the next generation of detectors.…”
Section: A Comparison With Minimal Supersymmetrymentioning
confidence: 99%
“…where D m , c QNum , c uNum , c dNum , c HuNum , c HdNum and the complete analysis are again given in ref. [93].…”
Section: Pos(corfu2019)066mentioning
confidence: 99%
“…Η πρόβλεψη της µάζας του µποζονίου Higgs, η οπία συνέπεσε µε τα αποτελέσµατα του LHC (ATLAS [22,23] and CMS [24,25]) -σε συνδυασµό µε ένα σχετικά ϐαρύ υπερσυµµετρικό ϕάσµα-ήταν επιτυχία για το Πεπερασµένο (σε κάθε επίπεδο ϐρόχων) N = 1 υπερσυµµετρικό µοντέλο SU (5) [26], ενώ ένα άλλο πεπερασµένο µοντέλο (σε επίπεδο δύο ϐρόχων), το Πεπερασµένο N = 1 υπερσυµµετρικό µοντέλο SU (3) ⊗ SU (3) ⊗ SU (3) [27], επίσης συµφωνούσε µε τα πειραµατικά αποτελέσµατα. Επιπλέον, το παραπάνω πρόγραµµα εφαρµόστηκε και στην περίπτωση του Ελάχιστου Υπερσυµµετρικού Καθιερωµένου Προτύπου (ΕΥΚΠ) [28,29] µε επιτυχή αποτελέσµατα για τις µάζες των top και bottom κουάρκς και του µποζονίου Higgs, ϕέροντας ένα σχετικά ϐαρύ υπερσυµµετρικό ϕάσµα (παλαιότερες αναλύσεις περιγράφονται στο [30]). Ακόµα, είναι γνωστό ότι εάν το neu-tralino ϑεωρηθεί ως το Ελαφρύτερο Υπερσυµµετρικό Σωµατίδιο (ΕΥΣ), τότε αποτελεί πολύ καλό υποψήφιο για την ανακάλυψη της Σκοτεινής ΄Υλης (ΣΥ) [31].…”
Section: εισαγωγήunclassified
“…The Higgs mass prediction, which coincided with the LHC results (ATLAS [22,23] and CMS [24,25]) -combined with a predicted relatively heavy spectrum of SUSY particles -was a success of the all-loop finite N = 1 SUSY SU (5) model [26], while another finite theory, namely the N = 1 (two-loop) finite SU (3) ⊗ SU (3) ⊗ SU (3) [27], also confirmed the LHC results. Additionally, the above programme was also applied in the MSSM [28,29], with successful results concerning the top, bottom and Higgs masses, also featuring a relatively heavy SUSY spectrum (a review of past analyses can be found in [30]). Furthermore, it is a well known fact that the lightest neutralino, being the Lightest SUSY Particle (LSP), is an excellent candidate for Cold Dark Matter (CDM) [31].…”
Section: Introductionmentioning
confidence: 99%